To the Problem of Electromechanical Interaction in Elevators with Controlled Electric Drive and Fuzzy Speed Controller - A. S. Koval; A. V. Shvayakou (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers problems concerning electromechanical interaction in elevators with an adjustable asynchronous electric drive equipped with the vector control systems under direct torque control and direct torque control with pulse-width modulator. A mathematical description of electromechanical elevator system with due account of nonlinearity of the worm gear is given in the paper. The paper presents a simplified circuit design of a control system with a fuzzy speed controller. It has been established that the factor of electromechanical interaction in electromechanical system with the adjustable asynchronous electric drive and an fuzzy speed controller is within the range which corresponds to existence of the essential electromechanical interaction.